EVALUATION OF SEWAGE WITHIN MAKHACHKALA BY CHEMICAL PARAMETERS - A. Sh. Ramazanov; M. A. Kasparova; I. V. Saraeva (Юг России: экология, развитие, 2014)
Abstract. Theme. Assessment of the quality of wastewater within Makhachkala by chemical parameters.Location. Makhachkala, Dagestan, Russia.The aim of the study is to determine the chemical quality of sewage water polluting the Caspian Sea within the city of Makhachkala.Method. Object of study is the sample of wastewater sampled 10–11 January 2012 within the city of Makhachkala. Sampling of wastewater and chemical analysis was carried out in accordance with the International Organization for Standardization. Quality test samples evaluated in terms of water pollution index and coefficient calculation integrated pollution.Results. Using certified measurement techniques in 9 samples of wastewater identified 26 normalized parameters. Found that wastewater selected in two paragraphs refer to quality very dirty, 7 points extremely dirty; in all samples of wastewater content from 6 to 10 standardized components exceeds the MCL and the coefficient of the complex water pollution 7 samples belong to category II and contamination of sample 2 to Category III contamination.Main conclusion. The data obtained can be considered as the primary material for further chemical monitoring the quality of wastewater into the Caspian Sea within the administrative boundaries of the city of Makhachkala.